2016
DOI: 10.2147/vhrm.s91020
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapy with lercanidipine and enalapril in the management of the hypertensive patient: an update of the evidence

Abstract: Hypertension is an important risk factor for premature death as it increases the probability of stroke, myocardial infarction, and heart failure. Antihypertensive drugs can decrease cardiovascular (CV) morbidity and mortality. The majority of hypertensive patients need more than one antihypertensive agent to attain blood pressure (BP) targets. Monotherapy can effectively reduce BP only in 20%–40% of patients. Multiple mechanisms including increased peripheral vascular resistance, increased cardiac work, and hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…A few examinations have proposed other potential components. One theory recommends that lercanidipine causes lesser veno-tightening than different medications because of lower thoughtful initiation [11]. Fogari et al contemplated this distinction by assessing serum levels of norepinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…A few examinations have proposed other potential components. One theory recommends that lercanidipine causes lesser veno-tightening than different medications because of lower thoughtful initiation [11]. Fogari et al contemplated this distinction by assessing serum levels of norepinephrine.…”
Section: Discussionmentioning
confidence: 99%
“…When calcium channels blockers are used as mono-therapy, the possibility for stimulation of AT 1 R signaling should be taken into account. Notably, a recent meta-analysis, based on more than 40 studies, has shown that combination therapy that targets both the angiotensin system and the voltage gated calcium channels, will provide a better blood pressure control than mono-therapy that acts at one of these targets [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with low-moderate hypertension, Lercanidipine/Enalapril combination, significantly reduces SBP and DBP, assessed either as office BP, home BP or 24-hours BP monitoring. This effect is associated with high rate (45.0%-69.6%) of responder patients (SBP/ DBP decrease >20 mmHg/ 10 mmHg) or subjects with normal BP values 17,18 . The therapeutic efficacy of the combination has also been demonstrated in elderly 19 , in diabetic patients 20 and in obese subjects 21,22 .…”
Section: What Is the Evidence Of Lercanidipine/enalapril Antihyperten...mentioning
confidence: 99%